Análise do transcriptoma de flores de coffea arabica em plantas irrigadas - Santos, Thiely Patricia Fabian dos (2022)
Coffee is one of the most important agricultural product for economic and social development of tropical producing countries. Nowadays, climate change has been causing periods of drought and/or irregular rain distribution associated with high temperatures. These climate changes have been generating situations of plant water stress and causing significant losses for coffee farmers, affecting productivity and coffee quality. The uniformity and floral development of the coffee tree is extremely important for its productivity and quality, and it is highly affected by environmental conditions. Thus, aiming to understand the processes affecting plant flowering, this work proposes a transcriptome analysis of flowers collected at different parts of the plant under water stress conditions: irrigated and non-irrigated. The transcriptome data from Coffea Arabica L. were analyzed with the Galaxy platform, which uses precise and flexible software for bioinformatics analysis. RNAseq data, from flowers collected at different stages of development, at different plant heights, and also under irrigated and non-irrigated conditions, was analyzed and compared to identify differentially expressed genes. In the first comparison between flowers of non-irrigated plants collected from the three regions of the plants: apical, medial and basal, 92 genes differentially expressed between apical and medial, 58 genes differentially expressed between apical and basal, and 151 between medial and basal were identified. In the second comparison, flowers of irrigated plants in the medial and apical region were compared with flowers of non-irrigated plants in the same region respectively. We identified more up regulated genes for the flowers of irrigated plants, both in the medial region (450 genes) and the apical region (293 genes). In the third and last comparison, between the flowers of irrigated and non-irrigated plants, the analyzes showed 322 differentially expressed genes, of which 289 were positively regulated for irrigated plants, 281 of which were exclusive, that is, expressed only in irrigated plants. Regarding the upregulated genes under irrigated conditions, several correspond to genes that encode proteins overexpressed under water stress, such as stress-induced protein K1N2-like, nsLTPs and late embryogenesis abundant protein 1-like, for example. Overall, the results of the analyzes identified more genes differentially expressed in the flowers of irrigated plants. The work provided a panel of differentially expressed genes, both under irrigated/nonirrigated conditions, as well as in different parts of the plant. In this way, the knowledge of the modulation of the expression of these genes can help in coffee genetic improvement programs in relation to the choice of cultivars tolerant to water deficit.